Strategi Pengembangan Industri Kecil Keramik dengan Pendekatan Contingent Strategic Success Formula - Moh. Hartono (Jurnal Teknik Industri, 2007)
Many small industries have difficulties to survive or to develop their business. The CSSF (contingent strategic success formula) approach was used to analyze the formula of success strategy combining with internal and external factors of the companies, i.e. to measure, to estimate, and to forecast the condition of environmental companies in this time and the future. Measuring. The internal factors of the companies was aimed to know everything that improved so that follow the external needs condition in the future. In order to succeed in the future, companies need to follow the optimal internal and external condition with turbulence level by use three points of the marketing methods, are to build the product positioning at specific area business, to build a robust differentiation and to build the brand images or emotional relationship with customers.